Influence of resin cement rigidity on the stress distribution of resin-bonded fixed partial dentures - Penteado, Marcela M. [UNESP]; Tribst, João P. M. [UNESP]; Jurema, Ana L. B. [UNESP]; Saavedra, Guilherme S. F. A. [UNESP]; Borges, Alexandre L. S. [UNESP] (Taylor & Francis, 2019)
The mechanical properties of the adhesive cement used in resin-bonded fixed partial dentures (RBFPD) can modify the clinical performance of the rehabilitation. The goal of this study was to evaluate the influence of the elastic modulus of different cements on the stress distribution in RBFPD using finite element analysis. For that an anterior 3-unit prosthesis was modeled based in a stereolithography file. The model was meshed with tetrahedral elements and materials considered isotropic, linearly elastic and homogeneous. The force applied to the palatal area of the lateral incisor (pontic) at 45° was 100 N. The cements used presented 7 different elastic modulus (E): 2, 6, 10, 14, 18, 22 or 26 GPa. The total deformation, von-Mises stress and maximum principal stress criteria were used to calculate the results. The lower tensile stress occurred in the cement layer with E = 2 GPa [25.6 (canine) and 16.32 MPa (incisor)]. For the prosthesis, the model with the lower tensile stress [287 (canine) and 248 MPa (incisor)] occurred when the cement presented E = 26 GPa. In this way, the stress concentration may have its magnitude modified depending on the stiffness of the cement. Since more flexible cements concentrate less tensile stress in its structure, but allow an increased displacement of the prosthesis, which is friable and rigid and ends up concentrating more tensile stress at its connector. In that way the clinician should avoid the use of adhesive cement with lower elastic modulus due to it increases the stress concentration in the ceramic.
Keywords: adhesive prosthesis; Elastic modulus; finite element analysis; resin cement